The Issues And Challenges Of Implementation Of Ḥisbah In Zamfara State In Nigeria - Suleiman, Abubakar Rufai (2022)
Enjoining right and forbidding evil is the crux of the institution of Ḥisbah in Islam. Nevertheless, historical and juristic studies of the institution of Ḥisbah show that its scope has never remained fixed. The Islamic societies differed in their composition and complexities and faced different kinds of problems. Therefore, the nature of the steps taken by the Ḥisbah functionaries continued to change. The establishment of Ḥisbah in Zamfara state was not without some forms of oppositions. There have been always claims by various quarters that Ḥisbah in Nigeria in general and in Zamfara is unconstitutional thus render its activities as illegal. To make the scenario worse for Ḥisbah institution, there have always been claims on the misbehavior of the Ḥisbah personal and their incompetency in carrying out their duties. To examine those claims, this study will first highlight the concept of Ḥisbah in Islam. After that the position of Ḥisbah in Zamfara state in the light of the Nigerian Constitution and other relevant legislations will be evaluated.